Pengaruh Kinesio Taping Terhadap Nyeri Lateral Epicondylitis Pada Koki - Setiyaningsih, Rita; , Maskun Pudjianto, SMPh, M.Kes; , Totok Budi Santoso, S.Fis., MPH (2015)
Background: Lateral epicondylitis (LE) known as tennis elbow, is a painful condition that occurs on the lateral side of the upper arm near the elbow because extensor carpi radialis brevis degeneration. It is caused by repetitive motions of the wrist and arm over time. The work related to lateral epicondylitis is chef. The lateral epicondylitis symptoms are pain on the lateral elbow and pressure pain on epicondylus lateralis humeri, strengthened by test positive using cozen's test and maudsley test. Manu kinds of physiotherapy modality are used in this case, such as kinesio taping. Kinesio taping is tape elastic cab be used to reduce pain. Purpose: To known the effect of kinesio taping toward lateral epicondylitis pain to chef. Type of research: This research used quasi experiment method, with control group pre and post test design. Method of interpretation sample used purposive sampling technique. Measurement painful used PRTEE. The data were analyzed by SPSS with wilcoxon test. Result: In this research, each group is 5 people. Treatment group has a significant painful reduction (p < 0,05), shown by pre-test mean grade 52,2 and post-test grade 39,6. Whereas control group, pre-test mean grade 47,5 and post-test grade 49,5. Conclusion: It can be concluded that there in the effect of kinesio taping toward lateral epicondylitis to chef.